The Middle-Income Trap: Comparing Asian and Latin American Experiences - Jankowska, Anna (OECD Development Centre Policy Insights, 2012)
Chinese Taipei; Hong Kong, China; Korea and Singapore (the East Asian Newly Industrialised Countries or NICs) have been successful in attaining income convergence with high-income countries while Latin American countries remain caught in the Middle-Income Trap. The East Asian NICs pursued export-led growth by targeting strategic industries which facilitated gradual diversification and upgrading into new products that required similar skills and inputs. Comparing the experience of the NICs to Latin American economies reveals that successful diversification and upgrading of a country's export structure requires coherent and complimentary policies in the areas of education, infrastructure, innovation and access to finance